2016
DOI: 10.1155/2016/3045262
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of an Infected Nonunion of the Middle Third of the Femur Associated with Femoral Shortening in a Hemophilia Patient

Abstract: The management of nonunion and limb length discrepancy has remained a constant challenge in hemophilic patients. In this study, we aimed to present the treatment of femur infected nonunion and limb length discrepancy in a twenty-seven-year-old patient with hemophilia type A. A 27-year-old male patient with hemophilia type A referred to our institution for the treatment of right femur infected nonunion and 10 cm shortness of the femur. Resection of the nonunion site and bone-to-bone fixation with autologous bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Appropriate monitoring of bleeding and coagulant activity, as well as intensive support by a hematologist, are necessary for performing surgery in patients with hemophilia [19,20]. Nevertheless, the present case demonstrated that leg lengthening is a possible treatment option for the treatment of leg length discrepancies in patients with hemophilia.…”
Section: Discussionmentioning
confidence: 70%
“…Appropriate monitoring of bleeding and coagulant activity, as well as intensive support by a hematologist, are necessary for performing surgery in patients with hemophilia [19,20]. Nevertheless, the present case demonstrated that leg lengthening is a possible treatment option for the treatment of leg length discrepancies in patients with hemophilia.…”
Section: Discussionmentioning
confidence: 70%
“…However, many studies have shown that time of bone healing after fracture does not differ between patients with and without haemophilia . Even, Salduz et al reported a case of successful distraction osteogenesis using an external fixator in a haemophilic patient. In our study, there were no complications associated with bone union.…”
Section: Discussionmentioning
confidence: 99%
“…,39 Even, Salduz et al40 reported a case of successful distraction osteogenesis using an external fixator in a haemophilic patient. In our study, there were no complications associated with bone union.…”
mentioning
confidence: 99%
“…The most feared complication in fracture surgery is nonunion which is associated not only with bone loss and deformity but also frequently with infection [ 5 ]. Risk factors for nonunion are not only patient dependent such as gender, age, and comorbidities but also features of the fractures itself: open fractures, intraarticular, or comminuted fractures [ 3 ].…”
Section: Introductionmentioning
confidence: 99%